Artificial ground freezing of a volcanic ash: laboratory tests and modelling. Issue 3 (16th July 2014) - Casini, Francesca; Gens, Antonio; Olivella, Sebastia; Viggiani, Giulia M. B.
Abstract : The use of artificial ground freezing (AGF) to form earth support systems has had applications worldwide. These cover a variety of construction problems, including the formation of frozen earth walls to support deep excavations, structural underpinning for foundation improvement and temporary control of ground water in construction processes. On one hand, the main advantage of AGF as a temporary support system in comparison to other support methods, such as those based on injections of chemical or cement grout into the soil, is the low impact on the surrounding environment as the refrigerating medium required to obtain AGF is circulated in pipes and exhausted in the atmosphere or re-circulated without contamination of the ground water. On the other hand, the available methods may vary significantly in their sustainability and complexity in terms of times and costs required for their installation and maintenance. The ability to predict the effects induced by AGF on granular materials is therefore crucial to assessing construction time and cost and to optimising the method. In this work, the thermo-hydro-mechanical processes induced by artificial freezing of a soil body are studied using a constitutive model that encompasses frozen and unfrozen behaviour within a unified effective-stress-based framework. It makes use of a combination of ice pressure, liquid water pressure and total stress as state variables. The model is validated and calibrated using the results of a series of laboratory tests on natural samples of a volcanic ash (Pozzolana) retrieved during construction of Napoli underground, where the technique of AGF was used extensively to stabilise temporarily the ground and control the ground water.